2008
DOI: 10.1534/genetics.108.090399
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Arabidopsis Indole-3-Butyric Acid Response Mutants Defective in Novel Peroxisomal Enzymes

Abstract: Genetic evidence suggests that indole-3-butyric acid (IBA) is converted to the active auxin indole-3-acetic acid (IAA) by removal of two side-chain methylene units in a process similar to fatty acid boxidation. Previous studies implicate peroxisomes as the site of IBA metabolism, although the enzymes that act in this process are still being identified. Here, we describe two IBA-response mutants, ibr1 and ibr10. Like the previously described ibr3 mutant, which disrupts a putative peroxisomal acyl-CoA oxidase/ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
159
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(168 citation statements)
references
References 91 publications
(145 reference statements)
6
159
0
2
Order By: Relevance
“…Mutation of genes encoding the apparent b-oxidation enzymes INDOLE-3-BUTYRIC ACID RESPONSE1 (IBR1), IBR3, or IBR10 results in IBA resistance, but does not alter IAA response or confer a dependence on exogenous carbon sources for growth following germination (Zolman et al, 2000(Zolman et al, , 2007(Zolman et al, , 2008, consistent with the possibility that these enzymes function in IBA b-oxidation but not fatty acid b-oxidation.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…Mutation of genes encoding the apparent b-oxidation enzymes INDOLE-3-BUTYRIC ACID RESPONSE1 (IBR1), IBR3, or IBR10 results in IBA resistance, but does not alter IAA response or confer a dependence on exogenous carbon sources for growth following germination (Zolman et al, 2000(Zolman et al, , 2007(Zolman et al, , 2008, consistent with the possibility that these enzymes function in IBA b-oxidation but not fatty acid b-oxidation.…”
mentioning
confidence: 84%
“…Similarly, mutants defective in the peroxisomal ABC transporter PXA1, which may transport substrates into the peroxisome for b-oxidation (Zolman et al, 2001b), and mutants defective in several peroxisome-targeted enzymes, including the acyl-CoA oxidase double mutant acx1-2 acx2-1 (Adham et al, 2005), the branchedchain amino acid catabolism mutant chy1-10 (Zolman et al, 2001a), and the IBA response triple mutant ibr1-2 ibr3-1 ibr10-1 (Zolman et al, 2008), are IBA resistant and IAA sensitive ( Fig. 1A; Zolman et al, 2001aZolman et al, , 2001bZolman et al, , 2008Adham et al, 2005).…”
Section: Iba-resistant Mutants Are Defective In Iba-to-iaa Conversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, additional energy would be used up and might eventually lead to insufficient energy needed for cell growth and development. Zolman et al (2008) demonstrated that energy is needed in converting NAA to IAA, hence, displaying reduced responses of NAA in root elongation.…”
Section: Root Induction From In Vitro Leaf and Stem Explantsmentioning
confidence: 99%